Effect of Transepithelial Photorefractive Keratectomy without Mitomycin C in the Treatment of Femtosecond Laser In Situ Keratomileusis Corneal Flap Complications - Jing Wang; Weiqian Cao; Liming Tao (Journal of Ophthalmology)
Purpose. To assess the efficacy and safety of transepithelial photorefractive keratectomy (TPRK) without mitomycin C as treatment for femtosecond laser in situ keratomileusis (FS-LASIK) corneal flap complications. Methods. Eight patients with corneal flap complications that occurred after FS-LASIK (five with eccentric flaps, two with buttonhole flaps, and one with a thick flap) were included in the study. Patients were treated with TPRK without mitomycin C between two weeks and twelve months after surgery. The postoperative manifest refraction, uncorrected distance visual acuity, and haze formation were assessed during six months of follow-up. Results. The mean manifest refractive spherical and cylinder refraction was 0.16 ± 0.26 and −0.44 ± 0.33 diopters, respectively, at six months postoperatively. The uncorrected distance visual acuity was above 20/25 in all patients after six months of follow-up. No haze formation was detected. Conclusions. TPRK without mitomycin C appears to be a safe and effective treatment for FS-LASIK corneal flap complications.